(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This paper examines the size, composition and quality of public expenditure in three large Indian states Punjab, Gujarat and Rajasthan using audited figures up to FY 2021-22, revised estimates for FY 2022-23 and the latest available FY 2023-24 Budget Estimates (BE). It situates each state’s fiscal choices in the broader post-GST, post-pandemic macro-fiscal context, including the tapering of grants, the central push for state capital spending and pressures from committed expenditure and subsidies. The analysis finds: (i) Gujarat sustains a modest revenue surplus and mounts an aggressive capital outlay push in 2023-24; (ii) Rajasthan improves receipts and steps up capital outlay, but faces medium-term risks from the re-adoption of the Old Pension Scheme (OPS); and (iii) Punjab contends with a persistent revenue deficit and a very high ratio of committed expenditure to revenue receipts, with electricity subsidies weighing heavily on fiscal space. Cross-state contrasts underscore the trade-offs among subsidy design, pension policy and growth-enhancing capital spending. Policy recommendations focus on protecting capex, rationalising non-merit subsidies, strengthening public financial management (PFM) and improving discom and pension sustainability. Key figures cited are drawn from official budget analyses and authoritative fiscal surveys.